EMERGING DISPLAY TECHNOLOGIES FOR ORGANIC USER INTERFACES. - Co, Elise; Pashenkov, Nikita (Communications of the ACM, 2008)
The article discusses innovative computer displays. Emerging technologies, as well as creative use of existing ones, will make possible displays far more versatile than traditional, solid, rectangular devices. Organic light-emitting diodes (OLED) require no backlighting and could well form the basis for future displays capable of being bent or twisted. Flexible electrophoretic displays in irregular shapes have already emerged. Discrete light-emitting diodes can be distributed over flexible substrates to create bendable media.